2003
DOI: 10.2519/jospt.2003.33.11.671
|View full text |Cite
|
Sign up to set email alerts
|

Hip Strength in Females With and Without Patellofemoral Pain

Abstract: Study Design: Cross-sectional. Objectives: To determine if females with anterior knee pain are more likely to demonstrate hip abduction or external rotation weakness than a similar, asymptomatic, age-matched control group. Background: Diminished hip strength has been implicated as being contributory to lower-extremity malalignment and patellofemoral pain. The identification of reliable and consistent patterns of weakness in this population may assist health care professionals establish a more effective treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
492
8
24

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 613 publications
(551 citation statements)
references
References 36 publications
27
492
8
24
Order By: Relevance
“…5 Because we used a relatively unique means of reporting torque that controlled for individual variance due to height and weight, we additionally converted our strength measures for isometric HABD and HER into a percentage of bodyweight for further comparison to studies that did not use these corrections (TABLE 4). 26,38 At the conclusion of this intervention, hip strength values for women in this study were approaching those reported for healthy women.…”
Section: Secondary Outcome Measuresmentioning
confidence: 48%
See 1 more Smart Citation
“…5 Because we used a relatively unique means of reporting torque that controlled for individual variance due to height and weight, we additionally converted our strength measures for isometric HABD and HER into a percentage of bodyweight for further comparison to studies that did not use these corrections (TABLE 4). 26,38 At the conclusion of this intervention, hip strength values for women in this study were approaching those reported for healthy women.…”
Section: Secondary Outcome Measuresmentioning
confidence: 48%
“…Several authors have reported that females with PFPS demonstrate weaknesses of the hip external rotators and hip abductors. 11,17,26,30,31,36,37 During functional activities, especially single-leg activities, the hip muscles prevent hip adduction and internal rotation, which may result in dysfunctional lower extremity joint alignment and can lead to the development of PFPS. 20 …”
mentioning
confidence: 99%
“…4,17,29 In spite of the fact that intervention programs for the management of patients with PFPS include exercises aimed at improving the performance of the lateral hip musculature, we are aware of only 2 research reports that have investigated whether differences in hip strength exist between patients with PFPS and a control group. 12,20 Ireland et al 12 found that 15 female subjects with PFPS demonstrated 26% less hip abduction strength and 36% less hip external rotation strength when compared to 15 age-matched control subjects. In contrast, Piva et al 20 reported that there were no statistically significant differences in hip abduction or external rotation strength when 30 subjects with PFPS (17 females and 13 males) were compared with 30 age-and gender-matched control subjects.…”
Section: 726mentioning
confidence: 99%
“…Given the contradictory results from previous reports, 12,20 we also performed a secondary analysis where data from the involved limbs of symptomatic subjects were compared to the corresponding limbs of asymptomatic subjects. We hypothesized that females with unilateral PFPS would exhibit lower LSI values during strength testing compared to asymptomatic subjects.…”
Section: 726mentioning
confidence: 99%
See 1 more Smart Citation